Literasi Numerasi Siswa SMP dalam Menyelesaikan Soal Asesmen Kompetensi Minimum - Fahmy, Ahmad Faridh Ricky; Apriliyani, Destiana; Janah, Riyadlotul; Khoerunnisa (Circle: Jurnal Pendidikan Matematika, 2025)
Numeracy literacy is an essential competency for junior high school students, serving as a foundational skill for further education. This ability can be assessed through the Minimum Competency Assessment (Asesmen Kompetensi Minimum/ AKM). However, variations in students’ mathematical proficiency lead to differences in numeracy literacy achievement. This study employed a qualitative descriptive approach aimed at describing junior high school students’ numeracy literacy in solving AKM questions, based on their levels of mathematical ability. The research was conducted at SMPN 01 Sragi, involving three eighth-grade students (class VIII.9) selected as subjects through purposive sampling. Data were collected through written tests and analyzed according to numeracy literacy indicators, namely: comprehending information, applying concepts and strategies, and reasoning and drawing conclusions. Data validity was ensured through member checking, data presentation, and conclusion triangulation. The analysis revealed that students with high mathematical ability were classified in the proficient numeracy literacy category, as they fulfilled all numeracy literacy indicators. Students with moderate ability were categorized as functional, meeting only the indicators for applying concepts and strategies, and reasoning and concluding. Meanwhile, students with low mathematical ability fell into the basic category, as they only achieved the reasoning and conclusion-drawing indicator. Therefore, instructional approaches incorporating contextual, real-life problems are crucial to train and enhance students’ numeracy literacy in addressing authentic real-world challenges.